Integrasi Kearifan Lokal Bangka Belitung pada Pengembangan Bahan Ajar Tanaman dalam Meningkatkan Nilai Konservasi Keanekaragaman Hayati - faishal bustan dinar; Sri Wuryastuti (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2022)
Based on the results of a preliminary study in grade 4 of Mendobarat State Elementary School 2. It was found that it was difficult for students to follow the teaching materials in Theme 3 so that there needed to be improvements in the teaching process so as not to cause problems, such as students being less interested in exploring learning, the media used by educators were thematic books whose material was too general. (R&D) is the method chosen to complete this research in order to get good and accountable results products in the world of education, especially at the elementary school. Through the 7 stages used during research according to what was expressed by Gall and Borg, namely starting from the potential and problems, to the product revision stage which of course has been carried out optimally by researchers in order to obtain valid and interesting books for students. The data collected is done using interview techniques, questionnaires, and documentation. The research has a target to elaborate plant teaching materials based on local wisdom of Bangka Belitung in increasing the conservation value of interesting biodiversity for students. Analyze data (preliminary study analysis, student questionnaires data analysis and expert justification questionnaires). Based on the results of making plant textbook based on local wisdom Bangka Belitung grade IV Elementary School, obtained plant textbooks that are interesting for students based on questionnaires that have been made students enjoy using this textbook. Sourced from the results of product trials at UPTD State Elementary School 2 Mendobarat with a percentage of 98,33%. While the textbooks were declared valid based on the result of the material expert’s justification, namely 84%, the verification of media design experts, 86% and the justification of learning practitioners, which was 92%. All the validation results are categorized “very valid”.